DETERMINAN PERILAKU MEROKOK REMAJA DI KOTA PONTIANAK - Ridha, Abduh; Hernawan, Andri Dwi (JURNAL BORNEO AKCAYA, 2015)
Non-communicable diseases cause 60% of deaths in Indonesia. Non-communicable disease risk groups getting younger. One reason is the age of new smokers become younger from year to year. School proved to be an effective setting for smoking reduction program in adolescents group. Schools is one of Free Smoking Area that regulated by the Government of Pontianak by Perda 10 tahun 2010. The main objective of this research is develop a model of relationship between health education, the influence of interpersonal (family and friends), advertising exposure, and knowledge with smoking cessation among high school students in Pontianak. The study was designed with cross-sectional. The study was conducted on high school students in Pontianak, West Kalimantan, in the period May 2013-April 2014. Data were analyzed by multivariate analysis using logistic regression to get the model. From multivariable analysis is known if the teens which have a family of smokers, smoker friends, exposure to cigarette advertising in the high category, has a habit of watching tv on mid night as well as having the knowledge that it has a low probability of smoking behavior by 99.3%. Based on the same formula, of the five factors that influence smoking behavior variables knowledge is the dominant factor. Cigarette advertising is the smallest triger. Model of adolescent smoking behavior of high school in Pontianak is mathematically capable of predicting the behavior of smoking to 99.3%, with the calibration of 0939 and 0777 amounted to discrimination.